Men's Sheds and Mentoring Programs: Supporting Teenage Boys' Connection with School - Wilson, N.; Cordier, Reinie; Wilkes-Gillan, S. (ICDDR,B: Centre for Health and Population Research, 2014)
The successful transition from boyhood to manhood is one of the most important male life transitions. Teenage boys at risk of school exclusion, and thus social exclusion, face added difficulties when school participation becomes dysfunctional. Men's Sheds are community-based male-friendly places where men can connect with other members of their communities, while simultaneously providing opportunities to learn practical skills and develop new interests. Many Australian Men's Sheds are offering intergenerational mentoring programs, usually based on shared construction projects, specifically targeted at teenage boys who are considered at risk. This paper presents descriptive qualitative data about one such intergenerational mentoring program. Data were collected from interviews with 4 teenage boys, a school Transition Advisor, and written teacher evaluations. Descriptive findings suggest that such programs offer some teenage boys a positive space to learn, socialise, promote tangible notions of community service, and reinforce respectful relationships in the supportive presence of older men.